Characteristics of Particle Cement Board and Wood Plastic Composite from Oil Palm (Elaeis guineensis Jacq.) Fronds - Rindayatno; Agus Nur Fahmi (International Journal of Scientific Multidisciplinary Research, 2024)
The yield of oil palm fronds is 8.4 tons/ha/year [1], a huge potential that has not been used optimally. Particle Cement Board (PCB) is a biocomposite that uses inorganic adhesive, namely cement, to bind biomass particles into a board. Wood Plastic Composite (WPC) is a biocomposite that combines plastic and biomass particles molded into boards. This study used the same biomass particles—oil palm fronds—to analyze the properties of PCBs and WPCs. Characteristics assessment by measuring and testing physical and mechanical properties were density, moisture content, water absorption, thickness swelling, elasticity (MOE and MOR), and internal bond strength (IBS) of oil palm fronds PCB (refers and compared to JIS A 5417-1992 and SNI 8299-2017 standards) and WPC (refers and compared to JIS A 5908-2003 and SNI 03-2105-2006 standards). The test results on the PCB are density 1.143 g/cm3, moisture content 8.429%, water absorption 26.414%, thickness swelling 1.368%, MoE 188.899 N/mm2, MoR 5.765 N/mm2, and IBS 0.054 N/mm2. The test results on the WPC are density 0.84 g/cm3, moisture content 2.36%, water absorption 16.21%, thickness swelling 7.11%, MoE 590.87 N/mm2, MoR 13.40 N/mm2, and IBS 0.31 N/mm2. Oil palm fronds is quite well used as a raw material for making particle cement board (PCB) and Wood Plastic Composite (WPC)